AN EXPLORATION OF SCHOOL NURSE ROLE IN SECONDARY GIRLS SCHOOLS IN BAHRAIN - Hassani, Ali A Rahim (LIFE: International Journal of Health and Life-Sciences, 2017)
The main role of the school nurse is to promote the health and wellbeing of students. Good health, in turn, fosters better academic outcomes. However, many schools in the Kingdom of Bahrain do not have school nurses. The few that have lack clear guidelines on their roles and responsibilities. The aim of this qualitative study was to explore the roles of school nurses in Bahrain and the barriers they encounter in their work. The study recruited 10 secondary school nurses and gathered their responses using semi-structured interviews. The responses were analysed using Burnard’s four-stage thematic analysis framework. The study found the main roles of school nurses are providing direct health care to students and staff, organising health promotion programs and surveillance of infectious diseases. The main barriers to school nurses are role conflict, the lack of professional autonomy and collaboration, and high student-nurse ratio. The study concluded that professional nursing programs and structured coordination between the Ministries of Health and Education are important to ensure school nurses clearly understand their roles and to improve their service delivery.